106 FUNGAL INFECTIONS IN CHILDREN: FREQUENCY, ASSOCIATIONS, OUTCOMES, AND MANAGEMENT. (1st January 2006) - Dolan, M.; Galjour, C.; Islam, S.
Abstract : Infections with fungi are usually very serious and may be increasing in incidence in pediatric inpatients. The underlying factors leading to this increase are not fully understood. We reviewed our experience from a single institution with pediatric fungal infections. Methods: The hospital microbiology database was searched for cultures of fungi in the Children's Hospital during an 18-month period from January 2004-June 2005. The medical records were reviewed and data pertaining to demographics, cultures, outcomes, antimicrobial use, and hospital course were collected and analyzed. Results: A total of 43 cases were noted in the period. Of these, a majority (77%) were in the NICU. The case-specific mortality rate was 20.9%, with most of it (78%) in the neonatal age. Average age was 13 months (range 0.25-132), and 65% were males. Prematurity, respiratory distress syndrome, and intraventricular hemorrhage were the commonest associated features. Eighty-four percent of patients were on antibiotics at the time of fungal isolation, with 70% on multiple drugs. The commonest antimicrobial used was vancomycin (58%), followed by aminoglycosides (47%) and ampicillin (42%). Fungus was cultured from the blood in 42 cases (98%), with occasional cultures from the urine, sputum, and peritoneum. Cultures stayed positive for four or greater blood draws in 58% of patients indicating prolonged clearance times. The commonest isolate was C. albicans (58%) followed by C. parapsilosis (33%). Amphotericin formulations were used in 91% cases with 35% combined with fluconazole. Central lines were found in 49% of cases. Average ICU stay was 92 days and total stay 101 days. Conclusions: Fungal infections are common in our patients with most in the NICU. Broad-spectrum antimicrobial use was noted in most at the time of fungal infection. Mortality rate is higher in this group compared to a similar cohort. This study indicates potential areas for infection control and rational antimicrobial use. Based on these results, we will plan a prospective study of fungal infections in children.